Impact of pump position on postoperative outcomes in less invasive left ventricular assist device implantation - Tomoyuki Suzuki; Tomoyuki Suzuki; Hayato Ise; Robin Döpp; Patric Kröpil; Patric Kröpil; Yoshikatsu Saiki; Artur Lichtenberg; Udo Boeken; Hug Aubin; Payam Akhyari; Yukiharu Sugimura (Frontiers in Cardiovascular Medicine)
Introductionless invasive approach (LIS) has recently become increasingly used for left ventricular assist device (LVAD) implantation. However, the impact of surgical access on pump position and clinical outcomes comparing LIS-LVAD implantation to full sternotomy (ST) has not been well discussed.MethodsBetween April 2010 and February 2021, a total of 237 consecutive patients received a LVAD, 76 (32.1%) of whom underwent the LIS approach and 161 (67.9%) of whom underwent ST. The clinical outcomes were retrospectively reviewed, and data of 66 comparable patients from each group extracted by propensity score matching were analyzed. For the analysis of pump position, cannula coronal angle (CCA,°) and pump diaphragm depth (PDD, mm) of LVAD were measured according to postoperative chest x-ray.ResultsThe mean age of all patients was 57.7 ± 11.3 years, 204 cases were male (86.1%), and 48 cases resulted in in-hospital death (20.3%). There was no significant impact on clinical outcomes according to surgical approach in matched groups. There was also no significant difference regarding pump position between two different access groups. A larger PDD was associated with both in-hospital death (60.2 ± 25.8 vs. 43.4 ± 31.3, P < 0.01) and death on LVAD (55.4 ± 28.1 vs. 41.7 ± 31.5, P < 0.01). Receiver operating characteristic (ROC) curve analyses revealed that PDD was a significant predictor of mortality in LIS approach.ConclusionsOur results indicate that LVAD implantation via LIS approach is safe yielding comparable outcomes with ST approach. Regarding spatial positioning of LVAD via LIS approach, larger PDD, may predict worse clinical outcomes.